Noncollinear antiferromagnetic textures driven high-harmonic generation from magnetic dynamics in the absence of spin-orbit coupling. (29th March 2023) - Ly, Ousmane
Abstract: We demonstrate the generation of high order harmonics in carrier pumping from precessing ferromagnetic or antiferromagnetic orders, excited via magnetic resonance, in the presence of topological antiferromagnetic textures. This results in an enhancement of the carrier dynamics by orders of magnitude, enabling for an emission deep in the THz frequency range. Interestingly, the generation process occurs in an intrinsic manner, and is solely governed by the interplay between the s-d exchange coupling underlying the noncollinear antiferromagnetic order and the dynamical s-d exchange constant of the magnetic drive. Therefore, the relativistic spin–orbit interaction is not required for the emergence of high harmonics in the pumped currents. Accordingly, the noncollinear topological antiferromagnetic order is presented as an alternative to spin–orbit interaction for the purpose of harnessing high harmonic emission in carrier pumping. Furthermore, we demonstrate the emergence of high harmonics from random magnetic impurities. This suggests the universality of the magnetically induced high harmonic emission in the presence of real and/or momentum space noncollinear textures. Our proposal initiates a tantalizing prospect for the utilization of topological textures in the context of the highly active domains of ultrafast spintronics and THz emission.